Managing Partners and Management Professionals: Institutional Work Dyads in Professional Partnerships. (13th June 2013) - Empson, Laura; Cleaver, Imogen; Allen, Jeremy
Abstract: This study presents an empirical analysis of the micro‐dynamics of institutional work. Examining the 'corporatization' of large international law firm partnerships, the study identifies the dyadic relationship that develops between two different types of professionals, the managing partner and management professional, and demonstrates how their relationship becomes a key mechanism for institutional work. The study shows how, by working together, these individuals take advantage of differences in their relative social positions: specifically their formal authority, specialist expertise, and social capital. The study identifies seven forms of institutional work in which they engage and demonstrates how these multiple forms simultaneously encompass the creation, maintenance, and disruption of the institution of partnership. The study argues that this simultaneous occurrence helps to account for the phenomenon of sedimentation, whereby the gradually emerging institutional logic of the corporatized partnership is being integrated into the traditional partnership form.